Regulation of matrix synthesis rates by the ionic and osmotic environment of articular chondrocytes. - Urban, J; Hall, A; Gehl, K (1993)
Chondrocytes in cartilage are embedded in a matrix containing a high concentration of proteoglycans and hence of fixed negative charges. Their extracellular ionic environment is thus different from that of most cells, with extracellular Na+ being 250-350 mM and extracellular osmolality 350-450 mOsm. When chondrocytes are isolated from the matrix and incubated in standard culture medium (DMEM; osmolality 250-280 mOsm), their extracellular environment changes sharply. We incubated isolated bovine articular chondrocytes and cartilage slices in DMEM whose osmolality was altered over the range 250-450 mOsm by Na+ or sucrose addition. 35S-sulphate and 3H-proline incorporation rates were at a maximum when the extracellular osmolality was 350-400 mOsm for both freshly isolated chondrocytes and for chondrocytes in cartilage. The incorporation rate per cell of isolated chondrocytes was only 10% that of chondrocytes in situ both 4 and 24 hours after isolation. For freshly isolated chondrocytes, the rate increased 30-50% in DMEM to which NaCl or sucrose had been added to increase osmolality. In chondrocytes incubated overnight in DMEM, the rate was greatest in DMEM of normal osmolality and fell from the maximum in proportion to the change in osmolality. The effects of sucrose addition on incorporation rates were similar but not identical to those of Na+ addition. Changes in cell volume might be linked to changes in synthesis rates since the cell volume of chondrocytes (measured by Coulter-counter) increased 30-40% when the cells were removed from their in situ environment into DMEM. Synthesis rates can thus be partly regulated by changes in extracellular osmolality, which in cartilage is controlled by proteoglycan concentration. This provides a mechanism by which the chondrocytes can rapidly respond to changes in extracellular matrix composition.